Silicon carbide-diamond composite substrate and application

By setting an interface layer in the silicon carbide-diamond composite material, the problem of poor thermal conductivity and uniformity of existing composite materials is solved, and the uniformity of high thermal conductivity and light transmittance is achieved, which is suitable for heat dissipation applications of high-power electronic devices.

CN119812142APending Publication Date: 2025-04-11SICC SHANGHAI CO LTD

Patent Information

Application Number
CN202510017299.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Due to lattice mismatch, interface bonding problems and interface thermal resistance problems, existing silicon carbide-diamond composite materials are difficult to achieve better thermal conductivity and light transmittance, as well as uniformity of large-size areas, especially the problem of gradually deteriorating uniformity from center to edge.

Method used

An interface layer is provided in the silicon carbide substrate layer and the polycrystalline diamond layer to reduce the interface thermal resistance between layers, improve the thermal conductivity of the composite substrate, and reduce the difference between the silicon carbide substrate layer and the polycrystalline diamond layer, avoid delamination, and ensure the integrity of the crystal morphology.

Benefits of technology

High thermal conductivity and light transmittance are achieved, and the uniformity of thermal conductivity is maintained in large-size composite substrates, avoiding thermal conductivity differences in the center and edge regions, and greatly improving the heat dissipation performance and power density of high-power electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812142A_ABST
    Figure CN119812142A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon carbide-diamond composite substrate and application, and belongs to the field of semiconductor materials. The silicon carbide-diamond composite substrate is characterized by sequentially comprising a silicon carbide substrate layer, an interface layer and a polycrystalline diamond layer from bottom to top, the thermal conductivity of the silicon carbide-diamond composite substrate is greater than or equal to 650 (W / (m.K)); the light transmittance is greater than or equal to 26%; the diameter is not less than 1 inch. According to the silicon carbide-diamond composite substrate, the interface layers are arranged in the silicon carbide substrate layer and the polycrystalline diamond layer, on one hand, the interface thermal resistance between the layers can be reduced, and the overall thermal conductivity of the composite substrate can be improved; on the other hand, the difference between the silicon carbide substrate layer and the polycrystalline diamond layer is reduced, delamination of the silicon carbide substrate layer and the polycrystalline diamond layer is avoided, and the composite substrate with complete crystal morphology is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a silicon carbide-diamond composite substrate and its application, belonging to the field of semiconductor materials. Background Art

[0002] Silicon carbide (SiC) is a wide bandgap material. The third-generation semiconductor represented by SiC has excellent characteristics such as high temperature resistance, high voltage resistance, high frequency, high power and radiation resistance. Traditional Si devices and their integrated circuits are not suitable for operating temperatures above 250°C, and it is difficult to withstand high radiation, high power and high frequency environments. Among the many wide bandgap materials, SiC materials have outstanding performance. Compared with the currently commonly used Si devices, its operating temperature can be increased by 3 times, the operating frequency can be increased by 10 times, the current can be increased by 100 times, and the loss is greatly reduced. In high-temperature electronic applications, SiC is a reliable material to replace Si. As power electronic devices and optical devices develop towards high power, integration, and miniaturization, the devices will generate a lot of heat during operation. If the heat cannot be effectively dissipated, the device temperature will rise rapidly, resulting in aging of materials and devices, performance degradation, and even failure. The development of a heat dissipation substrate with high thermal conductivity can efficiently export the heat generated by the device, thereby ensuring the effective operation of the device.

[0003] Diamond has many extremely excellent properties, one of the most important properties is its extremely high thermal conductivity, which is as high as 2200 (W / (m·K)). At the same time, diamond itself is a very good insulating material and can be an excellent heat dissipation material for high-power optoelectronic components. Therefore, diamond and silicon carbide have excellent material properties, such as high thermal conductivity, high electric field strength and high electron mobility. These properties combined can significantly improve the heat dissipation performance and power density of high-power electronic devices; silicon carbide-diamond composite substrates can also maintain stable performance in extreme environments such as high temperature, radiation resistance and corrosion resistance, and are suitable for aerospace, military and deep-sea exploration. In addition, silicon carbide-diamond composite substrates are compatible with existing semiconductor manufacturing processes, which can reduce barriers to technology transformation, improve resource utilization and economy, and promote the widespread application of wide bandgap semiconductor materials in the fields of electronics and optoelectronics.

[0004] In the prior art, for silicon carbide and diamond composite materials, due to the lattice mismatch problem between silicon carbide and diamond, serious interface bonding problem and interface thermal resistance problem, it is difficult for silicon carbide and diamond composite materials to achieve good thermal conductivity and transmittance as well as uniformity over large areas, especially there is a problem of gradually deteriorating uniformity from the center to the edge. Summary of the invention

[0005] In order to solve the above problems, a silicon carbide-diamond composite substrate is provided. By setting an interface layer in the silicon carbide substrate layer and the polycrystalline diamond layer, on the one hand, the interface thermal resistance between the layers can be reduced and the overall thermal conductivity of the composite substrate can be improved; on the other hand, the difference between the silicon carbide substrate layer and the polycrystalline diamond layer is reduced to avoid delamination of the two, so as to obtain a composite substrate with complete crystal morphology.

[0006] According to one aspect of the present application, a silicon carbide-diamond composite substrate is provided, comprising the following features:

[0007] (1) From bottom to top, it includes a silicon carbide substrate layer, an interface layer and a polycrystalline diamond layer;

[0008] (2) Thermal conductivity of silicon carbide-diamond composite substrate ≥ 650 (W / (m·K)); light transmittance ≥ 26%;

[0009] (3) Diameter ≥ 1 inch.

[0010] Specifically, the present application provides a silicon carbide-diamond composite substrate of a larger size, which has higher thermal conductivity and transmittance based on its larger size; the silicon carbide-diamond composite substrate includes a silicon carbide substrate layer, an interface layer and a polycrystalline diamond layer. The provision of the interface layer can, on the one hand, reduce the interface thermal resistance between layers and improve the overall thermal conductivity of the composite substrate; on the other hand, it reduces the difference between the silicon carbide substrate layer and the polycrystalline diamond layer, avoiding delamination of the two, so as to obtain a composite substrate with a complete crystal morphology.

[0011] Preferably, the thermal conductivity of the silicon carbide-diamond composite substrate is ≥810 (W / (m·K)); the light transmittance is ≥36%;

[0012] Optionally, the silicon carbide-diamond composite substrate is divided into a plurality of square regions with a side length of 3 mm×3 mm, and a thermal conductivity value of each square region is obtained;

[0013] The thermal conductivity standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤22, and the thermal conductivity standard deviation coefficient refers to the ratio of the thermal conductivity standard deviation calculated from all square areas to the thermal conductivity mean.

[0014] The silicon carbide-diamond composite substrate of the present application can be divided into several small square areas, and the above parameters can prove that the thermal conductivity distribution of the silicon carbide-diamond composite substrate is relatively uniform. Assuming that the silicon carbide-diamond composite substrate is divided into n areas by the above division method, and the thermal conductivity value of each area is the average thermal conductivity value of the area, then n thermal conductivity values ​​are obtained.

[0015] The n thermal conductivity values ​​are calculated to obtain the mean thermal conductivity and standard deviation of the n regions. The thermal conductivity standard deviation coefficient = thermal conductivity standard deviation / thermal conductivity mean. The smaller the value, the smaller the numerical difference and discreteness of the n regions, which means that the thermal conductivity uniformity of the silicon carbide-diamond composite substrate is better.

[0016] Optionally, K1-K2≤275 (W / (m·K)), K1 represents the maximum value of thermal conductivity in all square regions, and K2 represents the minimum value of thermal conductivity in all square regions.

[0017] The n thermal conductivity values ​​obtained in n regions are compared with each other, the maximum value is K1, and the minimum value is K2. K1-K2 represents the fluctuation range of the thermal conductivity of the silicon carbide-diamond composite substrate, and is the parameter most affected by extreme values. Therefore, the smaller K1-K2 is, the smaller the difference in extreme values ​​of the silicon carbide-diamond composite substrate is, and it can also indicate that the thermal conductivity uniformity of the silicon carbide-diamond composite substrate is better.

[0018] Preferably, the thermal conductivity standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤12, and the thermal conductivity standard deviation coefficient refers to the ratio of the thermal conductivity standard deviation calculated for all square areas to the thermal conductivity mean; K1-K2≤150 (W / (m·K)), K1 represents the maximum value of thermal conductivity in all square areas, and K2 represents the minimum value of thermal conductivity in all square areas.

[0019] The currently prepared silicon carbide-diamond composite substrates are difficult to achieve improved thermal conductivity and uniform distribution of thermal conductivity, resulting in large differences in thermal conductivity between the center and edge areas of the silicon carbide-diamond composite substrates. In particular, the larger the size and the higher the thermal conductivity of the silicon carbide-diamond composite substrate, the greater the difference in thermal conductivity, which is generally manifested as a gradual deterioration in quality from the center to the edge of the substrate, making it difficult to meet industrial applications.

[0020] The silicon carbide-diamond composite substrate provided in the present application has strong uniformity of thermal conductivity, which improves the problem of poor uniformity of thermal conductivity that large-sized silicon carbide-diamond composite substrates in the prior art easily have.

[0021] Optionally, the silicon carbide-diamond composite substrate is divided into a plurality of square regions with a side length of 10 mm×10 mm, and a transmittance value of each square region is obtained;

[0022] The transmittance standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤19, and the transmittance standard deviation coefficient refers to the ratio of the transmittance standard deviation calculated from all square areas to the transmittance mean.

[0023] Optionally, T1-T2≤10%, T1 represents the maximum value of the light transmittance in all the square regions, and T2 represents the minimum value of the light transmittance in all the square regions.

[0024] Similarly, the above parameters can indicate that the more concentrated the transmittance distribution of the silicon carbide-diamond composite substrate is, the better the uniformity is.

[0025] Preferably, the transmittance standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤8.5, and the transmittance standard deviation coefficient refers to the ratio of the transmittance standard deviation calculated for all square areas to the transmittance mean; T1-T2≤6.5%, T1 represents the maximum transmittance in all square areas, and T2 represents the minimum transmittance in all square areas.

[0026] Optionally, the grains of the silicon carbide-diamond composite substrate are crystallized along the (100) plane, and the grains are evenly arranged.

[0027] Optionally, the grain size of the interface layer is 5 to 16 μm, and the axial deviation angle of the grain is less than 6.5°;

[0028] The grain size of the polycrystalline diamond layer is 75-125 μm, and the axial deviation angle of the grain is less than 19°.

[0029] Specifically, the silicon carbide-diamond composite substrate provided by the present application realizes controllable grain size and direction due to the presence of the interface layer, so that the grains crystallize along the (100) direction, and the axial deviation angle of the grains in the interface layer is less than 6.5°; the grain size is 5 to 16 μm, and the axial deviation angle of the grains in the polycrystalline diamond layer is less than 19°; the grain size is 75 to 125 μm, and the grains are evenly arranged, so the uniformity of the grain size and the grain deviation angle is good, thereby reducing the transmission loss of phonons and photons, and improving the uniformity of thermal conductivity and transmittance of the silicon carbide-diamond composite substrate.

[0030] Preferably, the grain size of the interface layer is 5 to 5.5 μm, and the axial deviation angle of the grain is less than 3.8°;

[0031] The grain size of the polycrystalline diamond layer is 75-80 μm, and the axial deviation angle of the grain is less than 11°.

[0032] According to another aspect of the present application, there is provided a method for preparing a silicon carbide-diamond composite substrate, comprising the following steps:

[0033] (1) Preparation before growth: etching the silicon carbide substrate;

[0034] (2) Interface layer growth: methane is used as the reaction gas, hydrogen is used as the carrier gas, and oxygen is used as the auxiliary gas, and chemical vapor deposition is used to grow on the etched silicon carbide substrate at a growth temperature of 600-700°C to obtain an interface layer;

[0035] (3) Growth of polycrystalline diamond layer: The amount of methane, hydrogen and oxygen is adjusted and the growth is continued at a growth temperature of 950-1050°C. After the growth is completed, a polycrystalline diamond layer is obtained, i.e., a silicon carbide-diamond composite substrate.

[0036] Specifically, in the process of preparing the silicon carbide-diamond composite substrate, the present application first grows to form an interface layer, and the grains formed in the interface layer are small and uniform, and have better adaptability to the growth of the carbon surface, which is conducive to achieving a uniform transition between the silicon carbide substrate and the polycrystalline diamond layer. The present application bonds diamond and silicon carbide through the grains of the interface layer to form a nested structure, thereby achieving fixed bonding between the silicon carbide substrate and the polycrystalline diamond layer, avoiding the phenomenon of fracture or delamination of silicon carbide and diamond, and improving the overall light transmittance; on the other hand, the presence of the interface layer reduces the interface thermal resistance between the silicon carbide substrate and the polycrystalline diamond layer, and improves the overall thermal conductivity and uniformity.

[0037] Specifically, the growth temperature in step (2) is 600-700°C, wherein it can be 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C;

[0038] Specifically, the growth temperature in step (3) is 950-1050°C, wherein it can be 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C, 1010°C, 1020°C, 1030°C, 1040°C or 1050°C.

[0039] Optionally, in step (2), the growth time is 2 to 5 hours.

[0040] Specifically, in step (2), the growth time can be 2 h, 3 h, 3.5 h, 4 h or 5 h.

[0041] Specifically, in step (2) of the present application, the growth temperature is strictly controlled, and then the growth rate is controlled, and low-temperature nucleation growth is performed to obtain a dense and uniform interface layer of grains, thereby achieving fixed bonding of silicon carbide and diamond.

[0042] Optionally, in step (3), the growth time is 24 to 168 hours.

[0043] Optionally, in step (2), the amount of hydrogen used is 300 to 1000 sccm, the amount of methane used is 5% to 7% of the amount of hydrogen used, and the amount of oxygen used is 0.1 to 0.2% of the amount of hydrogen used.

[0044] Specifically, the present application makes specific restrictions on the amount of hydrogen, methane and oxygen used, which interact with the temperature to control the growth of the interface layer.

[0045] In the above steps (2) and (3), if the amount of hydrogen used increases, the cost will increase, and if the amount is reduced, black spot defects will be more likely to occur. The addition of oxygen can also inhibit the formation of amorphous carbon, thereby inhibiting the generation of black spot defects; in step (2), the growth temperature is low and the methane excitation is weak. The methane amount is 5% to 7% of the hydrogen amount, which is beneficial to increase the methane reaction concentration. However, too high a methane concentration will lead to uncontrollable grain size and disordered polycrystalline orientation; a low methane concentration will lead to slow growth; a specific amount of oxygen is beneficial to eliminate black spot defects.

[0046] In addition, the present application makes specific restrictions on the amount of hydrogen, oxygen and methane used. The amount of hydrogen and oxygen used can not only improve the uniformity of the distribution of methane during growth, so that a uniform interface layer can be uniformly deposited on the silicon carbide substrate, and a polycrystalline diamond layer can be uniformly deposited on the interface layer, but also improve the uniformity of the temperature on the growth surface in step (2) and step (3), and reduce the temperature difference between the edge and the center, so as to obtain a composite substrate with a high degree of consistency.

[0047] Optionally, in step (3), the amount of hydrogen used is 300-1000 sccm, the amount of methane used is 3%-4% of the amount of hydrogen used, and the amount of oxygen used is 0.1-0.2% of the amount of hydrogen used.

[0048] Preferably, the amount of hydrogen used in step (2) is 300-500 sccm, and the amount of hydrogen used in step (3) is 500-700 sccm.

[0049] Specifically, the present application makes specific restrictions on the amount of hydrogen used in step (2) and step (3), which are adapted to the temperatures of step (2) and step (3), respectively. When the temperature is low but the amount of hydrogen used is large, the plasmatization of hydrogen cannot be guaranteed, thereby affecting the diamond deposition effect, and further having an adverse effect on thermal conductivity and transmittance; when the temperature is high but the amount of hydrogen used is small, it will lead to a decrease in deposition rate, a prolonged deposition time, and an increase in production costs.

[0050] Optionally, the amount of methane used in step (3) is 50 to 80% of the amount of methane used in step (2).

[0051] Optionally, the temperature rising rate during step (2) to step (3) is 5 to 100° C. / min.

[0052] Preferably, the temperature rising rate during step (2) to step (3) is 10 to 20° C. / min.

[0053] Specifically, if the temperature rise rate during the process from step (2) to step (3) is too high, the grain orientation uniformity will be poor, the grains will be too large, etc., affecting the thermal conductivity, transmittance and uniformity; if the temperature rise rate during the process from step (2) to step (3) is too slow, the sedimentation rate will decrease, the deposition time will be extended, the production cost will increase, and it will be not conducive to commercial production.

[0054] Specifically, in step (3), the temperature is increased to grow a polycrystalline diamond layer and the amount of methane is reduced to avoid uncontrollable grain size and disordered polycrystalline orientation.

[0055] Optionally, the etching in step (1) is performed in a hydrogen-oxygen plasma atmosphere for 0.5 to 2 hours, and in the hydrogen-oxygen plasma atmosphere, 1%≤O2:H2≤4%.

[0056] Specifically, hydrogen and oxygen are used as reaction gases, and the hydrogen and oxygen gas molecules are excited into a plasma state, generating a large number of atoms, electrons, ions and free radicals. The active free radicals undergo oxidation and reduction reactions with the surface of silicon carbide, and high-energy ions physically bombard the surface of silicon carbide. By limiting the ratio of hydrogen and oxygen, etching time, and silicon carbide surface temperature, efficient and controllable etching can be achieved.

[0057] The above etching process makes the carbon surface of the silicon carbide substrate have a specific surface state, which is conducive to the crystallization and uniform arrangement of the diamond grains (100) plane, thereby obtaining the silicon carbide-diamond composite substrate of the present application with high thermal conductivity, light transmittance and better uniformity.

[0058] Optionally, in step (1), the surface temperature of the silicon carbide substrate is 950-1050° C., and Ra of the silicon carbide substrate is less than 0.2 nm.

[0059] Specifically, the size of the silicon carbide substrate is 1 to 4 inches, and the thickness is 200 to 500 μm.

[0060] Optionally, in step (3), after the growth is completed, a cooling step is also included, and the cooling rate is 2 to 5°C / min.

[0061] The above-mentioned cooling rate is relatively slow. Firstly, it can avoid the separation and fracture of the silicon carbide substrate and the polycrystalline diamond layer during the cooling process; instead, it can achieve uniform annealing of the growing interface layer and the polycrystalline diamond layer, release the stress of the composite substrate, reduce the warping of the diamond polycrystalline substrate, and avoid introducing other defects.

[0062] According to another aspect of the present application, there is also provided application of the above-mentioned silicon carbide-diamond composite substrate in a semiconductor device.

[0063] The beneficial effects of this application include but are not limited to:

[0064] 1. According to the silicon carbide-diamond composite substrate of the present application, by setting an interface layer in the silicon carbide substrate layer and the polycrystalline diamond layer, on the one hand, the interface thermal resistance between the layers can be reduced and the overall thermal conductivity of the composite substrate can be improved; on the other hand, the difference between the silicon carbide substrate layer and the polycrystalline diamond layer is reduced to avoid delamination of the two, so as to obtain a composite substrate with complete crystal morphology.

[0065] 2. According to the silicon carbide-diamond composite substrate of the present application, the grain size and direction are controllable in both the interface layer and the polycrystalline diamond layer, and the grains are evenly arranged, which reduces the transmission loss of phonons and photons and improves the uniformity of thermal conductivity and transmittance of the silicon carbide-diamond composite substrate.

[0066] 3. The silicon carbide-diamond composite substrate according to the present application, in addition to having high thermal conductivity, transmittance, thermal conductivity uniformity and transmittance uniformity, also has good optical and mechanical properties, significantly improving the heat dissipation performance and power density of high-power electronic devices; and is compatible with existing semiconductor manufacturing processes, can reduce barriers to technology transformation, improve resource utilization and economy, and promote the widespread application of wide bandgap semiconductor materials in the fields of electronics and optoelectronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0068] Figure 1 This is a photo of the silicon carbide-diamond composite substrate involved in the embodiment of the present application.

[0069] Figure 2 This is a morphology diagram of the diamond interface layer in the silicon carbide-diamond composite substrate involved in Example 3 of the present application.

[0070] Figure 3 This is a surface morphology diagram of a polycrystalline diamond layer in a silicon carbide-diamond composite substrate involved in Example 3 of the present application. DETAILED DESCRIPTION

[0071] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0072] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application were purchased through commercial channels.

[0073] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.

[0074] Example 1

[0075] This embodiment relates to a method for preparing a silicon carbide-diamond composite substrate, which specifically includes the following steps:

[0076] (1) Preparation before growth: After cleaning, a silicon carbide substrate with Ra < 0.2 nm was placed on the surface of a molybdenum table. The surface temperature of the silicon carbide substrate was 950° C. and it was etched in a hydrogen-oxygen plasma atmosphere (1% ≤ O2:H2 ≤ 4%) for 0.5 h.

[0077] (2) Growth of interface layer: methane is used as the reaction gas, hydrogen is used as the carrier gas, oxygen is used as the auxiliary gas, the amount of hydrogen is 300 sccm, the amount of methane is 5% of the amount of hydrogen, the amount of oxygen is 0.1% of the amount of hydrogen, the growth temperature is 600°C, the growth time is 2 hours, and chemical vapor deposition is used to grow on the etched silicon carbide substrate to obtain the interface layer;

[0078] (3) Growth of polycrystalline diamond layer: adjusting the gas dosage of methane, hydrogen and oxygen, wherein the dosage of hydrogen is 300 sccm, the dosage of methane is 3% of the dosage of hydrogen, and the dosage of oxygen is 0.1% of the dosage of hydrogen. In the process from step (2) to step (3), the temperature rise rate is 5°C / min, the growth temperature reaches 950°C, and the growth is continued for 24 hours. After the growth is completed, a polycrystalline diamond layer is obtained, and the temperature is cooled at a cooling rate of 2°C / min to obtain a silicon carbide-diamond composite substrate.

[0079] Example 2

[0080] This embodiment relates to a method for preparing a silicon carbide-diamond composite substrate, which specifically includes the following steps:

[0081] (1) Preparation before growth: After cleaning, a silicon carbide substrate with Ra < 0.2 nm was placed on the surface of a molybdenum table. The surface temperature of the silicon carbide substrate was 1050°C and etched in a hydrogen-oxygen plasma atmosphere (1% ≤ O2: H2 ≤ 4%) for 2 h;

[0082] (2) Growth of interface layer: methane is used as the reaction gas, hydrogen is used as the carrier gas, oxygen is used as the auxiliary gas, the amount of hydrogen is 1000 sccm, the amount of methane is 7% of the amount of hydrogen, the amount of oxygen is 0.2% of the amount of hydrogen, the growth temperature is 700°C, the growth time is 5 hours, and chemical vapor deposition is used to grow on the etched silicon carbide substrate to obtain the interface layer;

[0083] (3) Growth of polycrystalline diamond layer: The gas dosage of methane, hydrogen and oxygen is adjusted, wherein the dosage of hydrogen is 1000 sccm, the dosage of methane is 4% of the dosage of hydrogen, and the dosage of oxygen is 0.2% of the dosage of hydrogen. In the process from step (2) to step (3), the temperature is increased at a rate of 100°C / min, the growth temperature reaches 1050°C, and the growth is continued for 168 hours. After the growth is completed, a polycrystalline diamond layer is obtained, and the temperature is cooled at a cooling rate of 5°C / min to obtain a silicon carbide-diamond composite substrate.

[0084] Example 3

[0085] This embodiment relates to a method for preparing a silicon carbide-diamond composite substrate, which specifically includes the following steps:

[0086] (1) Preparation before growth: After cleaning, a silicon carbide substrate with Ra < 0.2 nm was placed on a molybdenum table. The surface temperature of the silicon carbide substrate was 1000°C and etched in a hydrogen-oxygen plasma atmosphere (1% ≤ O2:H2 ≤ 4%) for 1 h.

[0087] (2) Growth of interface layer: methane is used as the reaction gas, hydrogen is used as the carrier gas, oxygen is used as the auxiliary gas, the amount of hydrogen is 400 sccm, the amount of methane is 6% of the amount of hydrogen, the amount of oxygen is 0.15% of the amount of hydrogen, the growth temperature is 650°C, the growth time is 3.5 hours, and chemical vapor deposition is used to grow on the etched silicon carbide substrate to obtain the interface layer;

[0088] (3) Growth of polycrystalline diamond layer: The gas dosage of methane, hydrogen and oxygen is adjusted, wherein the dosage of hydrogen is 500 sccm, the dosage of methane is 3.5% of the dosage of hydrogen, and the dosage of oxygen is 0.15% of the dosage of hydrogen. In the process from step (2) to step (3), the temperature is increased at a rate of 15°C / min, the growth temperature reaches 1000°C, and the growth is continued for 60 hours. After the growth is completed, a polycrystalline diamond layer is obtained, and the temperature is cooled at a cooling rate of 3°C / min to obtain a silicon carbide-diamond composite substrate.

[0089] Example 4

[0090] The difference between Example 4 and Example 3 is that the amount of methane used in step (2) is 9% of the amount of hydrogen used, and the rest are the same.

[0091] Example 5

[0092] The difference between Example 5 and Example 3 is that the amount of methane used in step (3) is 6% of the amount of hydrogen used, and the rest are the same.

[0093] Example 6

[0094] The difference between Example 6 and Example 3 is that the amount of oxygen used in step (2) is 0.05% of the amount of hydrogen used, and the rest are the same.

[0095] Example 7

[0096] The difference between Example 7 and Example 3 is that the amount of oxygen used in step (3) is 0.05% of the amount of hydrogen used, and the rest are the same.

[0097] Example 8

[0098] The difference between Example 8 and Example 3 is that in step (3), the amount of hydrogen used is 300 sccm, the amount of methane used is 3% of the amount of hydrogen used, and the rest are the same.

[0099] Example 9

[0100] The difference between Example 9 and Example 3 is that in step (3), the amount of hydrogen used is 600 sccm, the amount of methane used is 4% of the hydrogen used, and the rest are the same.

[0101] Example 10

[0102] The difference between Example 10 and Example 3 is that in the process from step (2) to step (3), the temperature rising rate is 120°C / min, and the rest are the same.

[0103] Comparative Example 1

[0104] The difference between Comparative Example 1 and Example 3 is that step (2) is not included, and the rest are the same.

[0105] Comparative Example 2

[0106] Comparative Example 2 is a method for preparing a diamond-SiC composite substrate with high thermal conductivity provided in Example 1 of Chinese Patent CN116121725A, and the specific steps are as follows:

[0107] 1) grinding the carbon surface of a 2-inch 4H-SiC substrate with a diameter of 50.8 mm with 5-7 micron diamond powder for 30 minutes; after grinding, the arithmetic average roughness Ra of the growth surface of the silicon carbide substrate is 30-100 nm, and the root mean square roughness Rq is 50-100 nm;

[0108] 2) Immerse the roughened SiC substrate in a suspension containing nano-diamonds and perform ultrasonic treatment for 20-40 minutes for seeding. The suspension containing nano-diamonds has the following components, by mass ratio: 0.1% to 10% of 1-2 micron nano-diamond powder, 50% to 80% of water, and 6% to 30% of dispersant sodium hexametaphosphate.

[0109] 3) then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 10 minutes respectively, the substrate was dried in nitrogen and then placed on a detachable substrate holder;

[0110] 4) The cleaned silicon carbide substrate is placed in the growth chamber of the MPCVD equipment, and the reaction gas methane CH4, hydrogen H2 as the carrier gas, nitrogen and oxygen as the auxiliary gas are introduced, and the diamond film is grown and deposited on the SiC substrate by microwave plasma chemical vapor deposition (MPCVD). Microwave heating is used during the growth process, and the microwave power, deposition pressure, and atmosphere ratio are adjusted to achieve a staged growth method. The growth is 60 hours; the heating, deposition pressure, and growth temperature are carried out in a multi-stage growth manner; it is divided into five stages: the first stage, the second stage, and the third stage. The first stage is the heating stage, in which the deposition pressure is gradually increased from 110 Torr to 140 Torr, the deposition pressure growth rate is 5 Torr every 3 hours, and the microwave power is gradually increased from 3000 W to 3600 W, so that the growth temperature gradually increases from 800 ° C to 900 ° C; the second stage is the stable stage, in which the deposition pressure, microwave power and growth temperature are kept stable; the third stage is the nucleation stage, in which the methane concentration is increased to 5%-20% to promote diamond nucleation;

[0111] The fourth stage is the multi-layer growth stage, with high-temperature interval growth at 900-1050°C and 1050-1300°C at an interval of 1:1. In the 900-1100°C growth stage, the methane concentration is 2%-10%, and the nitrogen concentration is 0.01%-0.1%; in the 1100-1300°C growth stage, the methane concentration is 2%-10%, and the oxygen concentration is 0.1%-0.5%, which promotes lateral growth and increases particle size.

[0112] The fifth stage is the cooling stage, by adjusting the deposition pressure to gradually decrease from 140 Torr to 110 Torr, the deposition pressure decrease rate is 5 Torr every 3 hours, and the microwave power is gradually reduced from 3600 W to 3000 W, so that the growth temperature gradually decreases from 900 ° C to 800 ° C;

[0113] The main reaction gas is methane, the carrier gas is hydrogen, and the auxiliary gases are nitrogen and oxygen in stages. The gas concentration is adjusted according to the needs of each stage to produce a diamond-SiC composite substrate with high thermal conductivity.

[0114] Comparative Example 3

[0115] The difference between Comparative Example 3 and Example 3 is that the growth temperature in step (2) is 1000° C., and the rest are the same.

[0116] Experimental Example 1

[0117] The thermal conductivity of the silicon carbide-diamond composite substrates obtained in Examples 1 to 10 and Comparative Examples 1 to 3 was tested using a harmonic method. The test results are shown in Table 1.

[0118] The silicon carbide-diamond composite substrate is divided into several square areas with a side length of 3mm×3mm, and each square area obtains a thermal conductivity value of the area; the thermal conductivity standard deviation coefficient refers to the ratio of the thermal conductivity standard deviation calculated for all square areas to the thermal conductivity mean.

[0119] K1 represents the maximum value of thermal conductivity in all square regions, and K2 represents the minimum value of thermal conductivity in all square regions.

[0120] The thermal conductivity in the second column of Table 1 refers to the average value of the thermal conductivity obtained from all test points in the composite substrate.

[0121] Table 1 Thermal conductivity measurement results

[0122]

[0123]

[0124] Experimental Example 2

[0125] The transmittance of the silicon carbide-diamond composite substrates obtained in Examples 1 to 10 and Comparative Examples 1 to 3 was tested. The specific testing method was the haze method. For diamond and silicon carbide materials, the higher the haze, the lower the transmittance. The test results are shown in Table 2.

[0126] The silicon carbide-diamond composite substrate is divided into several square areas with a side length of 10mm×10mm, and each square area obtains a transmittance value of the area; the transmittance standard deviation coefficient refers to the ratio of the transmittance standard deviation calculated for all square areas to the transmittance mean.

[0127] T1 represents the maximum value of the light transmittance in all the square areas, and T2 represents the minimum value of the light transmittance in all the square areas.

[0128] The light transmittance in the second column of Table 2 refers to the average light transmittance obtained from all test points in the composite substrate.

[0129] Table 2 Transmittance measurement results

[0130]

[0131]

[0132] Experimental Example 3

[0133] The silicon carbide-diamond composite substrates obtained in Examples 1 to 10 and Comparative Examples 1 to 3 were subjected to a grain arrangement test. The specific test method was a microscope combined with an X-ray diffraction test. The test results are shown in Table 3.

[0134] Table 3 Grain arrangement measurement results

[0135]

[0136]

[0137] It can be seen from Tables 1 to 3 that the thermal conductivity of the silicon carbide-diamond composite substrate provided in the embodiments of the present application is ≥650 (W / (m·K)); the transmittance is ≥26%; wherein, in Embodiments 1 to 3, the thermal conductivity of the silicon carbide-diamond composite substrate is ≥810 (W / (m·K)); the transmittance is ≥36%;

[0138] The thermal conductivity standard deviation coefficient of the silicon carbide-diamond composite substrate provided in the embodiment of the present application is ≤22, K1-K2≤275 (W / (m·K)), wherein in Embodiments 1 to 3, the thermal conductivity standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤12, K1-K2≤150 (W / (m·K));

[0139] The transmittance standard deviation coefficient of the silicon carbide-diamond composite substrate provided in the embodiment of the present application is ≤19, T1-T2≤10%, wherein the transmittance standard deviation coefficient of the silicon carbide-diamond composite substrate in embodiments 1 to 3 is ≤8.5, T1-T2≤6.5%;

[0140] The grain size of the interface layer of the silicon carbide-diamond composite substrate provided in the embodiment of the present application is 5-16 μm, and the axial deviation angle of the grains is less than 6.5°; the grain size of the polycrystalline diamond layer is 75-125 μm, and the axial deviation angle of the grains is less than 19°, wherein the grain size of the interface layer in embodiments 1 to 3 is 5-5.5 μm, and the axial deviation angle of the grains is less than 3.8°; the grain size of the polycrystalline diamond layer is 75-80 μm, and the axial deviation angle of the grains is less than 11°.

[0141] Depend on Figure 1 From the photo of the silicon carbide-diamond composite substrate, it can be seen that the overall uniformity of the silicon carbide-diamond composite substrate is good, and there is no black spot defect on the surface; Figure 2 and Figure 3 It can be seen that the diamond interface layer and the polycrystalline diamond layer of the silicon carbide-diamond composite substrate prepared in the present application have uniform grain arrangement, good uniformity of grain size and grain deviation angle, wherein the grain size of the diamond interface layer is smaller than that of the polycrystalline diamond layer.

[0142] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A silicon carbide-diamond composite substrate, characterized in that: Features include: (1) From bottom to top, it includes a silicon carbide substrate layer, an interface layer and a polycrystalline diamond layer; (2) Thermal conductivity of silicon carbide-diamond composite substrate ≥ 650 (W / (m·K)); light transmittance ≥ 26%; (3) Size ≥ 1 inch.

2. The silicon carbide-diamond composite substrate according to claim 1, characterized in that: The silicon carbide-diamond composite substrate is divided into a number of square areas with a side length of 3 mm×3 mm, and a thermal conductivity value of each square area is obtained; The thermal conductivity standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤22, and the thermal conductivity standard deviation coefficient refers to the ratio of the thermal conductivity standard deviation calculated from all square areas to the thermal conductivity mean.

3. The silicon carbide-diamond composite substrate according to claim 2, characterized in that: K1-K2≤275 (W / (m·K)), K1 represents the maximum value of thermal conductivity in all square regions, and K2 represents the minimum value of thermal conductivity in all square regions.

4. The silicon carbide-diamond composite substrate according to claim 3, characterized in that: The thermal conductivity standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤12, and the thermal conductivity standard deviation coefficient refers to the ratio of the thermal conductivity standard deviation calculated for all square areas to the thermal conductivity mean; and / or K1-K2≤150 (W / (m·K)), K1 represents the maximum value of thermal conductivity in all square regions, and K2 represents the minimum value of thermal conductivity in all square regions.

5. The silicon carbide-diamond composite substrate according to claim 1, characterized in that: The silicon carbide-diamond composite substrate is divided into a number of square areas with a side length of 10 mm×10 mm, and a transmittance value of each square area is obtained; The transmittance standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤19, and the transmittance standard deviation coefficient refers to the ratio of the transmittance standard deviation calculated from all square areas to the transmittance mean.

6. The silicon carbide-diamond composite substrate according to claim 5, characterized in that: T1-T2≤10%, T1 represents the maximum value of the light transmittance in all the square areas, and T2 represents the minimum value of the light transmittance in all the square areas.

7. The silicon carbide-diamond composite substrate according to claim 5, characterized in that: The transmittance standard deviation coefficient of the silicon carbide-diamond composite substrate is ≤8.5, and the transmittance standard deviation coefficient refers to the ratio of the transmittance standard deviation calculated from all square areas to the transmittance mean; and / or T1-T2≤6.5%, T1 represents the maximum value of the light transmittance in all the square areas, and T2 represents the minimum value of the light transmittance in all the square areas.

8. The silicon carbide-diamond composite substrate according to claim 1, characterized in that: The crystal grains of the silicon carbide-diamond composite substrate are crystallized along the (100) plane, and the crystal grains are evenly arranged.

9. The silicon carbide-diamond composite substrate according to claim 1, characterized in that: The grain size of the interface layer is 5 to 16 μm, and the axial deviation angle of the grain is less than 6.5°; The grain size of the polycrystalline diamond layer is 75-125 μm, and the axial deviation angle of the grain is less than 19°.

10. Use of the silicon carbide-diamond composite substrate according to any one of claims 1 to 9 in a semiconductor device.

Citation Information

Patent Citations

  • Preparation method of diamond-SiC composite substrate with adjustable thermal conductivity

    CN116121725A

Cited By

  • Diamond-silicon carbide composite substrate and preparation method and application thereof

    CN122094148A

  • Diamond-silicon carbide composite substrate, method for preparing the same and use thereof

    CN122094148B